Колекційні фонди тропічних і субтропічних рослин Донецького ботанічного саду НАНУ та їх інтродукція в захищений ґрунт - Gornitska, І.Р. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
Data about the tropical and subtropical plants collection fund composition and formation of the DBG of NAS of Ukraine are presented. Main directions and research methods, the most perspective centres of species mobilization for the introduction are cited.